Injuries and Overuse Syndromes in Rink Hockey Players - Husen, Martin; Burgsmüller, Lars; Burggraf, Manuel; Jaeger, Marcus; Dudda, Marcel; Kauther, Max (Sportverletzung · Sportschaden, 2023)
Rink Hockey is a high-speed low-contact sport with a widely recognized injury potential. Played with a hard ball by players wearing little or no protective gear, the rates of concussions and head injuries are of high interest. In this study, we reviewed and investigated injuries sustained by 108 German National League rink hockey players. We conducted an epidemiological cross-sectional study to determine sport-specific injuries and injury patterns in female and male rink hockey players. Data were collected by a standardized questionnaire. A total of 108 players participated in the study. The combined rate of injuries were 9.4/1000 athlete exposures. There was no significant difference between injury rates during games and practice. A sexspecific difference was not detected. Head injuries were the most frequent type (20.8 % of all injuries). Concussions made up 7 % of all head injuries with a rate of 0.76/1000 athlete exposure. Ball contact was the cause for 31 % of injuries, while player contact generated 26.2 % of all injuries. High rates of ball-contact-related injuries resulted in time loss and medical consultations. Head injuries were frequent, however did not result in significant time loss as compared to other injuries. The use of protective gear should be recommended.
Keywords: Rollhockey; Quadhockey; Verletzungen; Gehirnerschütterungen; Überlastungssyndrom